Efficacy of direct‐acting antivirals: UK real‐world data from a well‐characterised predominantly cirrhotic HCV cohort. Issue 11 (5th August 2019) - Macken, Lucia; Gelson, William; Priest, Matthew; Abouda, George; Barclay, Stephen; Fraser, Andrew; Healy, Brendan; Irving, Will; Verma, Sumita
Abstract: Direct‐acting antivirals (DAAs) have revolutionised the management of chronic hepatitis C virus (HCV) infection. We describe UK real‐world DAA experience. Individuals commencing HCV treatment containing a DAA regimen (Mar 2014‐Nov 2016), participating in the National HCV Research UK (HCVRUK) Cohort Study were recruited from 33 UK HCV centers. The data were prospectively entered at sites onto a centralised database. The data were reported as median (Q1‐Q3). Of the 1448 treated patients, 1054 (73%) were males, the median age being 54 years (47‐60), 900 (62%) being genotype 1 and 455 (31%) genotype 3. The majority, 887 (61%) had cirrhosis, and 590 (41%) were treatment‐experienced. DAA regimens utilised: genotype1 sofosbuvir (SOF)/Ledipasvir/±Ribavirin (625/900, 69%) and Ombitasvir/Paritaprevir/Dasabuvir/±RBV (220/900, 24%), and in genotype 3 SOF/Daclatasvir + RBV (256/455, 56%) and SOF/pegylated interferon/RBV (157/455, 35%). Overall, 1321 (91%) achieved sustained virological response (SVR12), genotype 1 vs 3, 93% vs 87%, P  < .001. Prior treatment, presence of cirrhosis and treatment regimen did not impact SVR12. Predictors of treatment failure were genotype 3 infection, OR, 2.015 (95% CI: 1.279‐3.176, P  = .003), and male sex, OR, 1.878 (95% CI: 1.071‐3.291, P  = .028). Of those with hepatic decompensation at baseline (n = 39), 51% (n = 20) recompensated post‐treatment, lower baseline serum creatinine being associated with recompensation ( P  = .029). There were two liver‐related deaths, both having decompensated disease. This real‐world UK data, comprising of a predominantly cirrhotic HCV genotype 1/3 cohort, confirms DAA efficacy with an overall 91% SVR12, with 51% recompensating post‐treatment. Genotype 3 infection was a predictor of treatment failure. Highlight: HCVRUK is one of the largest real world HCV databases. This study reports on real world outcomes of 1448 patients registered with HCVRUK (62% genotype 1 and 31% genotype 3), of whom about two‐thirds had cirrhosis and 40% were treatment experienced. Majority received a sofosbuvir‐based regimen. Overall 91% achieved SVR12. Genotype 3 infection and male gender were predictors of treatment failure.